2004
DOI: 10.1024/0300-9831.74.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Kinetic Characteristics of Purified and Isolated Green Tea Catechin Epigallocatechin Gallate (EGCG) after 10 Days Repeated Dosing in Healthy Volunteers

Abstract: This randomized, double-blind, placebo-controlled study assessed the safety, tolerability, and plasma-kinetic behavior of 94% pure crystalline epigallocatechin gallate (EGCG) after ten days' repeated dosing in 36 healthy male volunteers. Each of the three treatment groups consisted of 12 subjects; nine of them received oral EGCG in one dose of 200, 400, or 800 mg daily, and three received a placebo. Blood samples for plasma-kinetic EGCG characterization were taken on day 1 and day 10. Kinetic parameters for ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 22 publications
4
65
0
Order By: Relevance
“…Although considered safe and well tolerated, it was found that plasma C max of EGCG was several-fold higher when given after an overnight fast, as compared to the same dose given with food. This was also confirmed in a follow-up study were crystalline EGCG was administered to healthy subjects for 10 days after overnight fasting [39]. Combined, these studies consistently demonstrated that plasma concentrations of EGCG are significantly increased when GTE is consumed under fasting conditions.…”
Section: Pharmacokinetic and Safety Studiessupporting
confidence: 62%
See 1 more Smart Citation
“…Although considered safe and well tolerated, it was found that plasma C max of EGCG was several-fold higher when given after an overnight fast, as compared to the same dose given with food. This was also confirmed in a follow-up study were crystalline EGCG was administered to healthy subjects for 10 days after overnight fasting [39]. Combined, these studies consistently demonstrated that plasma concentrations of EGCG are significantly increased when GTE is consumed under fasting conditions.…”
Section: Pharmacokinetic and Safety Studiessupporting
confidence: 62%
“…With healthy volunteers as subjects, it was demonstrated that both of these catechin formulations exhibited similar pharmacokinetic profiles and were well tolerated at the dosages used (up to 800 mg/day for up to 4 wk) [37][38][39]. Subsequent studies increased these dosages even further, and also determined the effects of catechin administration after fasting or with food.…”
Section: Pharmacokinetic and Safety Studiesmentioning
confidence: 98%
“…The IC 50 and EC 50 values of EGCG on OATP1B3-mediated uptake of Fluo-3 and estrone-3-sulfate (8.4 and 10.5 M, respectively) and on OATP1B1-mediated transport of estrone-3-sulfate (IC 50 ϭ 7.8 M), are well within this range, indicating the physiological relevance of these interactions for those who take high-dose supplements. The same authors found that daily consumption of 800 mg of EGCG resulted in an average C max of 5.3 M after 10 days (Ullmann et al, 2004). In addition, the bioavailability of EGCG was shown to increase with increasing doses, indicating that a saturable presystemic elimination process is involved in the low systemic bioavailability (Chow et al, 2001).…”
Section: Effect Of Green Tea Catechins On Oatp Functionmentioning
confidence: 92%
“…This would include improvement of the 50% inhibitory-concentration value to reduce it from micromolar to nanomolar levels, potentially through chemical modifications to provide better coverage of the L43 loop, particularly in the area of the crucial residues L42 to L44, which remain largely accessible. The subinhibitory plasma levels of 200 to 300 nM available via oral administration (8,29) are less important, as the most likely use of this agent would be the acute removal of a sequestered parasite mass in people with severe malaria in a hospital setting where intravenous administration would be an option, although other routes of delivery would be beneficial. Further work will also be needed to assess the potential harmful effects of releasing large numbers of mature infected erythrocytes into the peripheral circulation and, in particular, their effect on the spleen.…”
Section: Discussionmentioning
confidence: 99%